Global Halal Supply Chains : Challenges and Strategies for Sustainable Trade - Askarova, Anel (2025)
This thesis examines the global Halal supply chains, focusing on their challenges and opportunities in achieving sustainable trade. As the Halal market rapidly expands beyond food into sectors like pharmaceuticals and logistics, the study analyzes cultural, economic, and regulatory factors shaping its development. Using trade data, SWOT analysis, and expert interviews, the research proposes strategies to enhance certification, logistics, and international cooperation in the Halal industry.